Coordinating across correctional, community, and VA systems: applying the Collaborative Chronic Care Model to post-incarceration healthcare and reentry support for veterans with mental health and substance use disorders - Bo Kim; Rendelle E. Bolton; Justeen Hyde; B. Graeme Fincke; Mari-Lynn Drainoni; Beth Ann Petrakis; Molly M. Simmons; D. Keith McInnes (BMC, 2019)
Abstract Background Between 12,000 and 16,000 veterans leave incarceration annually. As is known to be the case for justice-involved populations in general, mental health disorders (MHDs) and substance use disorders (SUDs) are highly prevalent among incarcerated veterans, and individuals with MHDs and SUDs reentering the community are at increased risk of deteriorating health and recidivism. We sought to identify opportunities to better coordinate care/services across correctional, community, and VA systems for reentry veterans with MHDs and SUDs. Methods We interviewed 16 veterans post-incarceration and 22 stakeholders from reentry-involved federal/state/community organizations. We performed a grounded thematic analysis, and recognizing consistencies between the emergent themes and the evidence-based Collaborative Chronic Care Model (CCM), we mapped findings to the CCM's elements - work role redesign (WRR), patient self-management support (PSS), provider decision support (PDS), clinical information systems (CIS), linkages to community resources (LCR), and organizational/leadership support (OLS). Results Emergent themes included (i) WRR - coordination challenges among organizations involved in veterans' reentry; (ii) PSS - veterans' fear of reentering society; (iii) PDS - uneven knowledge by reentry support providers regarding available services when deciding which services to connect a reentry veteran to and whether he/she is ready and/or willing to receive services; (iv) CIS - lapses in MHD/SUD medications between release and a first scheduled health care appointment, as well as challenges in transfer of medical records; (v) LCR - inconsistent awareness of existing services and resources available across a disparate reentry system; and (vi) OLS - reentry plans designed to address only immediate transitional needs upon release, which do not always prioritize MHD/SUD needs. Conclusions Applying the CCM to coordinating cross-system health care and reentry support may contribute to reductions in mental health crises and overdoses in the precarious first weeks of the reentry period.